(3JGQjN ONhd GdCJQGc Edi HdGO Gdjef hef edc Gdjef ef GdWhGFa GdoeNJdaI aj Ref GdESdGes
(3ChdgG (B:s
(3hHYO, agPG JGQjN ONhd GdCJQGc Edi CQV Gdjef hGdCcQGO GdeSdejf HGddhfO, hCejQge jheFP MSjf GdcQOi ai SfI (B922 s
(3BNQgG (B:s
(3adeG hba YGeQ Ydi gPg GdCHjGJ GdePchQI bGd(B: (3eCQGg EdGMbG Ke CNP YGeQ HYOgG HHQgI ef GdCjGe s
(3Vef eLehY , JQJjHgG (B: (3ef U (B213 - (3U(B231s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B77 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B(181) s
Keywords: (3GdJGQjNs